Facile microfluidic fabrication and characterization of ethyl cellulose/PVP films with neatly arranged fibers. (15th September 2022) - Rao, Jingshan; Shen, Chaoyi; Yang, Zhichao; Fawole, Olaniyi Amos; Li, Jiangkuo; Wu, Di; Chen, Kunsong
Abstract: Much attention and endeavor have been paid to developing biocompatible food packaging films. Here, ethyl cellulose (EC) and polyvinylpyrrolidone (PVP) were fabricated into films through a facile method, microfluidic spinning. Morphology observations showed that the fibers were neatly arranged with an average diameter of 1–4 μm. FTIR and X-ray diffraction analysis suggested the existence of good compatibility and interaction between EC and PVP. Thermogravimetric analysis demonstrated that PVP ameliorates the thermal properties; moreover, the tensile properties were improved, with tensile strength (TS) and Young's modulus up to 11.10 ± 1.04 MPa and 350.16 ± 45.46 MPa, respectively. The optimal formula was EC/PVP (2:3), of which the film displayed an enhanced TS of 4.61 ± 1.15 MPa and a modified water contact angle of 61.8 ± 4.4°, showing fine tensile and hydrophilic performance. This study provides a facile and green film fabrication method promising to be used for food wrapping. Graphical abstract: Unlabelled Image Highlights: Ethyl cellulose and polyvinylpyrrolidone were used as the precursors. Microfluidic spinning was used to produce micro-films with high surface area. Films of neatly arranged microfibers exhibiting good properties were fabricated. The films can be potentially used in food packaging applications.